Flood risk and residential real‐estate prices: Evidence from three US counties. Issue 2 (8th February 2022) - Miller, Ryan G.; Pinter, Nicholas
Abstract: This article analyzes residential property transactions to better understand the impact of urban flooding events and property distributions on the floodplain on real‐estate markets. We studied patterns before and after major fluvial flooding events in three counties that experienced such events between 2009 and 2013: Benton County, Oregon; Boulder County, Colorado; and Cass County, North Dakota. We tested for the presence and distribution of price discounting before and following these flood events using a hedonic difference‐in‐difference regression model. Floodplain discounts were detected in all three counties, over the full study period, including before and after flooding. However, only Boulder County exhibited a statistically significant price discount in the wake of the flooding event at the center of our analysis, with prices falling by 6.26% in the 100‐year floodplain until they rebounded after approximately 2–3 years. In Benton County, we were not able to detect a post‐flood price effect, but prices throughout the study period were 9.4% lower in the 100‐year floodplain compared to comparable properties outside the floodplain. Cass County experienced weaker discounting and only in the 500‐year floodplain, but a large flood control project was widely discussed after the 2009 flood event, which may have prevented widespread price discounting. The Boulder County case study confirms the phenomenon of post‐flood real estate discounting and subsequent rebound, as documented by other researchers. The other two case studies, interestingly, document that such discounting is not universal. We suggest that the difference seems to be explained by differing levels of pre‐flood local flood‐risk awareness, along with the magnitude of the triggering flood event. The new availability of nationwide real‐estate data allows for new and more detailed assessment of these important distinctions.